2022
DOI: 10.1007/s10459-022-10118-6
|View full text |Cite
|
Sign up to set email alerts
|

More than surgical tools: a systematic review of robots as didactic tools for the education of professionals in health sciences

Abstract: Within the field of robots in medical education, most of the work done during the last years has focused on surgeon training in robotic surgery, practicing surgery procedures through simulators. Apart from surgical education, robots have also been widely employed in assistive and rehabilitation procedures, where education has traditionally focused in the patient. Therefore, there has been extensive review bibliography in the field of medical robotics focused on surgical and rehabilitation and assistive robots,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 102 publications
(141 reference statements)
0
12
0
2
Order By: Relevance
“…Meanwhile, the surgical robot research literature database was established to integrate existing evidence‐based medical resources for robotic surgery treatment. This will greatly improve the efficiency of evidence‐based practice retrieval, saving as much of clinicians and managers' time as possible (Esagian et al, 2022; Li, Zhan, et al, 2022; Marcos‐Pablos et al, 2022; Niederberger & Deckert, 2022; Pacana & Siwiec, 2022; Tschann et al, 2022). Since the first da Vinci surgical robot was installed at the Gansu Provincial Hospital in January 2016, our hospital has completed more than 3000 robotic surgeries of various types, ranking among the top single‐operator surgical facilities nationally.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the surgical robot research literature database was established to integrate existing evidence‐based medical resources for robotic surgery treatment. This will greatly improve the efficiency of evidence‐based practice retrieval, saving as much of clinicians and managers' time as possible (Esagian et al, 2022; Li, Zhan, et al, 2022; Marcos‐Pablos et al, 2022; Niederberger & Deckert, 2022; Pacana & Siwiec, 2022; Tschann et al, 2022). Since the first da Vinci surgical robot was installed at the Gansu Provincial Hospital in January 2016, our hospital has completed more than 3000 robotic surgeries of various types, ranking among the top single‐operator surgical facilities nationally.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated its positive impact on the development of skills such as computational thinking, critical thinking, problem solving, creativity, motivation, and metacognitive skills [34][35][36][37][38]. According to the scientific literature, learning via robotics means that students learn knowledge from different areas, such as science and mathematics, and biosanitary content through the use of robots [38][39][40][41][42]. Despite this, there is very little scientific literature analyzing the influence of ER on improving curricular content, especially bioscience content, and existing studies usually focus on improving the knowledge and skills related to the robot itself and its handling [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…According to the scientific literature, learning via robotics means that students learn knowledge from different areas, such as science and mathematics, and biosanitary content through the use of robots [38][39][40][41][42]. Despite this, there is very little scientific literature analyzing the influence of ER on improving curricular content, especially bioscience content, and existing studies usually focus on improving the knowledge and skills related to the robot itself and its handling [40][41][42][43]. Benitti [44] and Ferrada [45] identified studies that presented the advantages of the use of ER in teaching content, including scientific content, at the Early Childhood Education stage [46], in Primary Education [47], or in Secondary Education [48].…”
Section: Introductionmentioning
confidence: 99%
“…There are different simulation models, some of high technology and complexity involving virtual tools, and some of human performance, both being expensive and available only in large centers. On the other hand, low-cost simulators (LCS) are a useful option for undergraduates and smaller training centers, as they reproduce surgical conditions with greater accessibility 5 .…”
Section: Introductionmentioning
confidence: 99%